Optimization of Aloe Vera Barbadensis Miller medium for Lactobacillus plantarum NBRC 3070 cultivation using Response Surface Methodology (RSM) / Hifa Nazirah Mohammed Yaziz - Mohammed Yaziz, Hifa Nazirah (2016)
Aloe vera has been hypothesized as an alternative prebiotic source for probiotic cultivation due to high content of carbohydrate. However, to date the use of Aloe vera as prebiotic has not been reported elsewhere. The aim of this study was to optimize Aloe vera medium supplemented with various carbon and nitrogen components to obtain the optimum Lactobacillus plant arum NBRC 3070 cell biomass production. Fractional Factorial Design (FFD) and steepest ascent were employed to identify the significant factors among the medium components on the cell growth and to approach proximity of optimum. Based on the screening step, maximum biomass production obtained was 11.816 logio CFU/ mL. As for regression analysis output, high Aloe vera compositions with glucose supplement were found to be influenced biomass production significantly (PO.05). Consequently, both factors were chosen for further step, steepest ascent. Result from the steepest ascent revealed that biomass production was increased with the increased of Aloe vera and glucose composition until up to 3.8% (v/v) and 5.5% (w/v), respectively. However, further increased in both components resulted in cell reduction. The highest L. plant arum NBRC 3070 biomass production was recorded at the 6th steepest ascent path with 10.105 logio CFU/ mL. Consequently, Aloe vera with 3.8% (v/v) and glucose with 5.5% (w/v) were used as a middle point in further optimization process. The optimum values were determined by Central Composite Design (CCD) under Response Surface Methodology (RSM) to optimize the use of Aloe vera and glucose. The statistical analysis showed that the optimal compositions of Aloe vera gel and glucose were at 3.65% (v/v) and 5.52% (w/v), respectively by setting the goal of optimization for biomass production to be at maximum level and the factor concentration in selected range. Predicted response in optimal conditions (9.98 logio CFU/ mL) was generated by the statistical tool. Based on the verification process, the experimental and predicted results were not significant difference (P>0.05) with low error percentage. The optimized Aloe vera and glucose medium allowed a highest cell biomass production up to 9.86 logio CFU/ mL which 18% higher than in de Man Rogosa Sharpe (MRS) cultivation medium. The optimized Aloe vera-glucose medium was further tested with other probiotic strains (Lactobacillus casei ATCC 393, Lactobacillus reuteri ATCC 55730, Lactobacillus acidophilus ATCC 4356 and Bifidobacterium pseudocatenulatum ATCC 27919) and it has been proved that this optimized medium was able to support their growth. Based on carbohydrate profiling, both Aloe vera gel and glucose were utilized by L. plantarum NBRC 3070 throughout cultivation process as carbon source for growth. Meanwhile, pH profiling showed the reduction of pH value occurred during cultivation due to organic acid produced from carbohydrate metabolism.